The cognitive turn in literary and artistic studies - Gracia Gaspar, María Luz (Escritura e Imagen, 2023)
At the beginning of the 21st century, a paradigm shift has begun in the human and social sciences that has affected literary and artistic studies and is known as the cognitive turn. It is characterised by the application of neuroscience and cognitive psychology to disciplines such as anthropology, linguistics, literary theory, philosophy and aesthetics. Specifically, in literary studies, the cognitive turn has led to the theory named as cognitive poetics and, in artistic studies, to neuroaesthetics. This paper presents the most relevant characteristics that the cognitive turn has unleashed in the field of literary studies, with a greater focus on the narrative genre, and in artistic studies.
Keywords: Cognitive sciences; literary theory; aesthetics; cognitive poetics; neuroaesthetics